Perancangan Sistem Pendukung Keputusan Pemilihan Supplier Pada Cv. Twinnies Baby Shop Jambi Menggunaan Metodesimple Multi Attribut Rating Technique (Smart): Design of a Decision Support System for Supplier Selection at CV. Twinnies Baby Shop Jambi Using the Simple Multi-Attribute Rating Technique Method (SMART) - The, Elizabeth; Ibnu Sani Wijaya; Hendri (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Abstract− CV. Twinnies Baby Shop, located in Jambi, still applies supplier selection based on subjective leadership decisions. This approach carries the risk of errors in determining suppliers, which could ultimately result in losses for the company. To address this issue, a decision support system was developed using the PHP programming language and MySQL database, supported by waterfall development methodology. Designed using Unified Modeling Language (UML), this system provides information on suppliers, admins, criteria, sub-criteria, and supplier evaluation results. Additionally, the system helps determine the best supplier using the Simple Multi-Attribute Rating Technique (SMART). With this system, the supplier selection process becomes more effective, structured, and objective, supporting more accurate decision-making for the company.